Enhancement on antioxidant, anti-hyperglycemic and antibacterial activities of blackberry anthocyanins by processes optimization involving extraction and purification - Wu, Han; Di, Qing-Ru; Zhong, Liang; Zhou, Jian-Zhong; Shan, Cheng-Jun; Liu, Xiao-Li; Ma, Ai-Min (Frontiers in Nutrition, 2022)
This research aimed to recover anthocyanin-rich extracts from blackberry (Rubus spp. Hull cultivar) by optimizing the processing conditions, and to characterize anthocyanin individuals and determine influences of optimization on enhancement of antioxidant and anti-hyperglycemic activities of anthocyanins as natural supplements. The ethanol concentration of 69.87%, HCl dosage of 0.53%, solid-to-liquid ratio of 1:19.06 at 47.68 ℃ for 17.04 h were optimal to obtain the highest extraction yield of anthocyanins at 0.72 mg/g. By using AB-8 macroporous resins, the anthocyanin concentration of 3.0 mg/mL, ethanol concentration of 90%, and elution rate of 2.0 mL/min were selected to boost the anthocyanin purity up to be 60.11%. Moreover, the purified anthocyanin extracts from blackberry contained nine main pigments which could be divided into three aglycone-based forms, and cyanidin-3-O-glucoside was the most abundant among them. Due to the successive processes of extraction and purification, the blackberry purified anthocyanin extracts (BA-PAE) showed much higher bioactive capacities than the blackberry crude anthocyanin extracts (BA-CAE) and blackberry fruit slurry extracts (BA-FSE), e.g. DPPH and ABTS radical scavenging activities (EC50 = 0.08 and 0.04, 0.32 and 0.24, and 1.31 and 0.41 mg/mL), oxygen radical absorbance capacity (1.60, 0.59, and 0.15 mmol TEAC/g), cytoprotective effects against oxidative stress in PC12 cells (1.69-, 1.58-, and 1.50-fold cell viability compared to oxidative group), α-amylase and α-glucosidase inhibitory activities (IC50 = 0.10 and 0.06, 0.56 and 0.32, 3.98 and 2.16 mg/mL), and antibacterial activity (93.23, 40.85%, and 80.42% reduced biofilm).